Twitter sentiment analysis for foreign exchange market prediction - Oon, Xue Ting (2019)
The goal of the project is to predict the result of the GBP/USD currency pair; whether the closing price is lower or higher than opening price, based on tweets collected. The tweets were from Twitter accounts with great influence such as politicians like the 44th and 45th president of the United States of America; Barack Obama and Donald Trump, as well as news outlets such as CNN, BBCWorld.